2021
DOI: 10.1590/0001-3765202120201347
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward synthesis of cytosporone analogs AMS35AA and AMS35BB

Abstract: Cytosporones, a class of octaketide resorcinolic lipids, have drawn the attention of researchers for exhibiting a number of notable biological properties. Herein, we describe routes to synthesize the bioactive synthetic resorcinolic lipids AMS35AA and AMS35BB with excellent overall yields using 3,5-dimethoxybenzoic acid as the starting material. The methods proved remarkably effi cient to achieve the target compounds and comprise the synthesis of AMS35AA catalyzed by ascorbic acid (vitamin C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Phthalide 1 was readily prepared by treating 3,5-dimethoxybenzoic acid with octanoyl chloride in the presence of AlCl 3 . This compound has been characterized by 1 H and 13 C NMR spectroscopy, and the data match those reported in the literature [ 1 ].…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Phthalide 1 was readily prepared by treating 3,5-dimethoxybenzoic acid with octanoyl chloride in the presence of AlCl 3 . This compound has been characterized by 1 H and 13 C NMR spectroscopy, and the data match those reported in the literature [ 1 ].…”
Section: Methodssupporting
confidence: 66%
“…Resorcinolic lipids, such as cytosporones and their precursors, can interact with the phospholipid bilayers [ 1 ], help in the formation of liposomes [ 2 ], promote protection against oxidative stress [ 3 ], and inhibit bacterial growth [ 1 , 2 ] and tumor cells [ 4 ]. In addition, the resorcinol lipid cytosporone B induced apoptosis in tumor cells by interacting with the nuclear orphan receptor Nur77 [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9,19 Additionally, the analogs are neither genotoxic nor mutagenic and do not affect biochemical parameters. 8,9,19 Strong evidence has recently shown that AMS35AA, alone or associated with CYC, has no toxic effects on spermatogenesis, suggesting that it might be used in association with CYC in chemotherapy without adverse effects on testicular function. 20 In line with previous research endeavors, this study aimed to assess the effects of CYC in conjunction with AMS35BB on genetic toxicology models and several other biological characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent investigations, our group has demonstrated that three synthetic cytosporone analogs, termed AMS35AA , AMS35BB , and AMS049 , can enhance the mutagenic effect of cyclophosphamide ( CYC ) and induce apoptosis in mice (Figure ). ,, Additionally, the analogs are neither genotoxic nor mutagenic and do not affect biochemical parameters. ,, Strong evidence has recently shown that AMS35AA , alone or associated with CYC , has no toxic effects on spermatogenesis, suggesting that it might be used in association with CYC in chemotherapy without adverse effects on testicular function …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation